The Mediating and Moderating Role of Self-Efficacy in the Relationship Between Stress and Depression - Negi, Ajit Singh (Prabandhan: Indian Journal of Management, 2019)
The aim of the current study was to examine the mediating or moderating role of self-efficacy in the relationship between stress and depression among students. A total of 91 engineering students of 18 years of age were included in the study. General self-efficacy and DASS-21 questionnaire were used for measurement in the present study. Hierarchical regression analysis and Sobel test were used to investigate the impact of the mediator in the relationship between stress and depression. The results determined that self-efficacy acted as a partial mediator between stress and depression. Further, the results of the interaction effect revealed that self-efficacy acted as a partial moderator between stress and depression. The study suggests that the regulation of self-help training programs, which focus on strengthening the mindful activities should be incorporated in the educational curriculum to enhance the self-efficacy of the students.